Pengaruh Hand Massage dan Aromaterapi Lavender terhadap Penurunan Nyeri Penusukan Jarum AV Fistula pada Pasien Hemodialisis - Artilla Raih Wiguna; Novika Andora; Sandra Andini (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Chronic kidney disease patients undergoing haemodialysis with AV fistula vascular access often experience pain during needle insertion. Recurrent pain can reduce patient comfort and quality of life, necessitating effective non-pharmacological nursing interventions. Hand massage and lavender aromatherapy are non-pharmacological interventions with relaxing and analgesic effects are known to have relaxing and analgesic effects that have the potential to reduce pain intensity. This study aimed to determine the effect of relaxation techniques such as hand massage and lavender aromatherapy on reducing pain during AV fistula needle insertion in chronic kidney disease patients at Bhayangkara Hospital, Bandar Lampung, in 2025. This study used a quasi-experimental design with a pre-test–post-test control group design. The sample size was 50, consisting of 25 in the intervention group and 25 in the control group, The findings are primarily applicable to patients with severe initial pain. The intervention group received hand massage and lavender aromatherapy, while the control group received standard care. Data analysis used within-group differences were analyzed using paired t-test, while between-group differences were analyzed using independent t-test. The average pre-test pain scale in the intervention group was 8.04 ± 0.93 and decreased to 4.28 ± 0.98 in the post-test. In the control group, the average pre-test pain score was 8.00 ± 0.91 and the post-test score was 6.92 ± 0.86. Bivariate analysis showed a significant reduction in pain in the intervention group with a p-value < 0.001 (p < 0.05). Hand massage relaxation techniques and lavender aromatherapy significantly reduced pain during AV fistula insertion in patients with chronic kidney disease. This intervention is recommended for use as a supportive therapy in nursing practice in haemodialysis units.